Design and Performance Test of Rubber Grinding Machine - Sri Aulia Novita; Hendra Hendra; Jamaluddin Jamaluddin; Muhammad Makky; Khandra Fahmi (Politeknik Pertanian Negeri Payakumbuh, 2019)
The quality of rubber processed materials, that is produced by the farmer is generally low and can be seen from their colour, pollutants levels, foul odour and the very cheap price. To improve the quality of the rubber should be done both in terms of its treatment and processing equipment. The main objective of this research is to enhance and improve the quality of farmer's rubber processed materials by using natural coagulant which liquid smoke to agglomerate the rubber, and designing of rubber grinding machine. The component of rubber grinding machine including hopper, regulating entry materials, three rollers, pulleys and belt, outlet, gears, engine, regulating the thickness and chassis. In this research, the thickness rubber after grinding is 3-5 mm accordance with Indonesian National Standard rubber. Processed material rubber produced is white and no pollutants. The coagulant used was liquid smoke with a concentration of 10 -20%, where this addition affects the agglomeration speed of rubber and smelled slightly of smoke. The average rate of Feed is 48.58 kg / h, a capacity of the machine is 37.40 kg/hr and cost of operation is Rp. 650 / kg.